The role of self-regulatory control processes in understanding aggressive ideations and behaviors: An experience sampling method study - Plessen, Kerstin Jessica; Constanty, Lauriane; Ranjbar, Setareh; Turri, Fiorella; Miano, Giorgia; Lepage, Caroline; Urben, Sébastien (Frontiers in Psychiatry, 2023)
Introduction In this study, we aimed to examine the association between aggressive ideations and aggressive behaviors in everyday life, as well as the role of processes related to self-regulatory control (i.e., self-control, ego depletion, and emotional states), using experience sampling methods (ESM). Methods A total of 62 male adolescents performed a baseline measure of aggression, violent ideations (trait level), and ESM assessments, including four measures per day during nine consecutive days. Results At a state level, aggressive ideations were associated with higher negative emotions during the previous day as well as with lower self-control and stronger anger rumination at the moment. Aggressive behaviors were related to higher anger rumination at the moment and to the manifestation of higher intensity of aggressive ideations derived in the previous measure. Higher self-control was related to a lower probability of aggressive behavior. Discussion This study highlights the temporal link between aggressive ideations and behaviors in everyday life as well as the role of self-control in understanding aggressivity in the lap of time. Furthermore, we observed that expressions of anger (i.e., reactivity, as well as rumination) were central in the understanding of aggressive ideations and behaviors in the everyday life (i.e., at within-person variability at the state level).